NEW TAXA OF HYPOPERLIDS (INSECTA: HYPOPERLIDA) FROM THE UPPER PERMIAN OF THE ARKHANGELSK REGION - Novokshonov V.G.; Aristov D.S. (My University, 2004)
Four new hypoperlid species of the genus Tshekardobia, Tsh. magnifica sp. nov., Tsh. lurida sp. nov., Tsh. panorpitincta sp. nov., and Tsh. maculitincta sp. nov. (suborder Hypoperlina), are described from the Soyana locality, Arkhangelsk Region, Kazanian Stage. Additionally, four hypoperlids of the suborder Strephocladina, Strephoneura tenebrosa sp. nov., S. vasta sp. nov., S. pallida sp. nov., and Graticladus severus gen. et sp. nov., are described from the same locality.
Keywords: hypoperlid; Paleozoic::Permian; Палеозой::Пермская